Instructional Design in Motion: Analyzing Short Arabic Learning Videos on Social Media through Gagne’s Nine Events of Instructions - Rini Marbianti; Moh Sholeh Afyuddin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to analyze the implementation of instructional components in short Arabic learning videos on social media based on Gagné’s Nine Events of Instruction, as well as to examine their implications for user engagement. This research employed a qualitative approach using content analysis of 50 purposively selected videos. The analysis was conducted by identifying the occurrence of instructional components and relating them to engagement indicators, including views, likes, comments, and saves. The findings reveal that the videos are dominated by the present content and gain attention components, while essential components such as stimulate recall of prior learning and assess performance are absent. These results indicate a gap between the ideal systematic instructional design and the actual practice of short-form video learning, which tends to be segmented and focused on delivering core content. Despite this limitation, the videos demonstrate a high level of engagement. This suggests that learning effectiveness in social media contexts is not solely determined by the completeness of instructional structure, but also by the content’s ability to capture attention and adapt to media characteristics and user behavior. Therefore, this study highlights a paradigm shift toward adaptive microlearning approaches and opens opportunities for developing more contextual instructional designs in the digital era.